A 33% Tuning Range High Output Power V-Band Superharmonic Coupled Quadrature VCO in SiGe Technology - Nasr, Ismail; Dudek, Manuel; Weigel, Robert; Kissinger, Dietmar (IEEE Radio Frequency Integrated Circuits Conference, 2012)
Abstract—This paper presents a wide tuning range superharmonic coupled quadrature Colpitts VCO with high output power. The circuit was fabricated using a low-cost SiGe technology with an ft/fmax of 200/250 GHz. The quadrature VCO employs a novel area efficient coupling technique that uses second harmonic coupling. Downcoversion mixers are implemented to provide an intermediate frequency signal, enabling easier measurement. A phase imbalance below 2 degrees is measured between the quadrature outputs, over a 6 GHz tuning range. The quadrature VCO can be tuned between 55 and 76.5 GHz having a record tuning range of approx. 33%. Moreover, the quadrature VCO has a maximum measured output power of +10.5dBm, and a minimum phase noise of -97 dBc/Hz. The overall chip draws 303mA from a 3.3V supply.
elib2cris::1512001600,nasr2012a
Keywords: Quadrature oscillator (QVCO); Colpitts; Wide tuning range; superharmonic coupling